To determine the value that correctly fills in the blank, we first need to calculate the left-hand side of the equation:
\[ 42 + 70 = 112 \]
Now, let's calculate the expression on the right-hand side, which is currently given as \( (6 + 10) \).
First, we add \( 6 + 10 \):
\[ 6 + 10 = 16 \]
Now we need to set the expressions equal to each other:
\[ 112 = 16 \]
Since this isn't correct, we must rewrite the expression on the right-hand side to reflect the correct total of 112.
One possible way to express this is:
\[ (6 + 10 + X) \quad \text{such that} \quad 16 + X = 112 \]
Solving for \( X \):
\[ X = 112 - 16 = 96 \]
Thus, the value that correctly fills in the blank is:
\[ \boxed{96} \]